Novel psychoactive substances: the pharmacology of stimulants and hallucinogens. Issue 7 (2nd July 2016) - Schifano, Fabrizio; Papanti, G. Duccio; Orsolini, Laura; Corkery, John M.
ABSTRACT: There are increasing levels of concern relating to the rapidly evolving novel psychoactive substances/NPS and web markets' scenarios. The paper aims at providing an overview of the clinical pharmacological issues related to some of the most popular NPS categories, e.g. stimulants and hallucinogens. NPS intake is typically associated with the imbalance of a complex range of neurotransmitter pathways/receptors, namely: dopamine; cannabinoid/CB1; and 5-HT2A . The intake is almost invariably undetectable with standard screening tests. Hence, it may frequently occur that the acute management of NPS misusers will need to focus on decreasing levels of both self/outward-directed aggression and agitation. Benzodiazepines may be considered as first line treatment. Alternatively, propofol and/or antipsychotics can be administered. Focus will be as well on treatment of possible rhabdomyolysis and hyperthermia. Indeed, future studies should inform better tailored management/treatment strategies.